2015
DOI: 10.1111/jpy.12308
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of nitrogen levels and mode of cultivation are viable methods to improve the lipid, fatty acids, phytochemical content, and bioactivities in Chlorella minutissima

Abstract: The effect of nitrogen (N: low = 2% N or moderate = 10% N) levels and cultivation (photoautotrophic or mixotrophic) modes on the biochemicals in Chlorella minutissima was evaluated using a mass culture system. Moderate N and mixotrophic cultures had higher biomass, protein, carbohydrate content and photosynthetic pigments than the low N and photoautotrophic treatments. In contrast, lipid and fatty acid content of the low N and photoautotrophic treatments were higher than in the moderate N and mixotrophic cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
(194 reference statements)
8
7
0
Order By: Relevance
“…extract was twice as active under N-replete conditions than under N-limited or starved conditions ( Figure 4 ). Those results are in agreement with the few studies that have evaluated the effects of N-limitation on antioxidant activities [ 25 , 29 , 35 , 36 ]. Çakmak et al [ 25 ] and Aremu et al [ 35 , 36 ] showed the negative impacts of N-starvation on the antioxidant activity of Chlamydomonas reinhardtii and Chlorella strains, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…extract was twice as active under N-replete conditions than under N-limited or starved conditions ( Figure 4 ). Those results are in agreement with the few studies that have evaluated the effects of N-limitation on antioxidant activities [ 25 , 29 , 35 , 36 ]. Çakmak et al [ 25 ] and Aremu et al [ 35 , 36 ] showed the negative impacts of N-starvation on the antioxidant activity of Chlamydomonas reinhardtii and Chlorella strains, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…However, the influence of nitrogen availability on antioxidant compounds is species-specific, and high antioxidant activity due to over-accumulation of secondary carotenoids under nutrient stress should not be generalized to all species. Indeed, only some chlorophytes species are able to accumulate secondary carotenoids [ 17 ], whereas several studies describe a decrease of antioxidant activity and primary carotenoids with N-starvation [ 25 , 29 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenols and flavonoids are the secondary metabolites more produced by microalgae when in detriment of UV exposure or under stress conditions induced by the culture medium. Those compounds are highlighted in cell protection and have an special role against the presence of harmful compounds [34,35,36]. Our results corroborate with the previous authors (Table 2), since microalgae biomasses were grown under UV radiation and used culture medium enriched with vinasse and NPK (EA-Cs2).…”
Section: Total Phenolic and Flavonoid Contentssupporting
confidence: 92%
“…Some studies demonstrate a ratio between presence/absence of UV radiation and the addition/restriction of nutrients with the synthesis of secondary metabolites. [36] Some bioactives have variation when produced by Chlorella minutissima grown with different doses of nitrogen in a mixotrophic and in a photoautotrophic systems, and the authors concluded the presence of this nutrient, especially in mixotrophic conditions, increased the production of secondary metabolites which reinforces our results. Under similar conditions, we've added NPK, with no detriment to carbon sources as the sugars from the vinasse, the nutrients were assimilated by C .sorokiniana during the dark periods, characterizing mixotrophic cultivation.…”
Section: Total Phenolic and Flavonoid Contentssupporting
confidence: 85%
“…However, biomass production has been achieved, and bioactive compounds have been obtained from microalgae isolated from extreme environments on Gran Canaria Island (Rodriguez‐Meizoso et al ). Several microalgae, such as species of Chlorella , Spirulina , Isochrisis , and Dunaliella , are widely recognized as potential sources of nutrients, including fatty acids, amino acids, minerals, and other essential compounds (Chu ; Aremu et al ; Greque de Morais et al ). In particular, the polyunsaturated fatty acid (PUFA) content in microalgae is difficult to predict at the levels of genus and species, making it difficult to select appropriate strains for biotechnological applications aimed at high lipid yield (Lang et al ).…”
Section: Introductionmentioning
confidence: 99%